ORANG TUA SEBAGAI PENANAM NILAI PANCASILA UNTUK ANAK USIA DINI DI ERA DIGITAL - Farah Ariani (Journal of Early Childhood Education (JECE), 2019)
The purpose of this scientific paper is to provide information on the importance of the role of parents in instilling the values of Pancasila for early childhood. Given the current degradation of Pancasila values in everyday life, especially in this digital era. The many shifts in values that occur as if to remind us again to strengthen the moral values of Pancasila. Pancasila as a way of life, state philosophy, state foundation and state ideology needs to be implemented and enforced in a planned, systematic and integrated manner for all components of the nation both state administrators and Indonesian citizens. This must start from the family environment.The acculturation of the value of Pancasila is the building of the nation's character (nation and character building) through the rediscovery of the values and the grounding of the Pancasila in order to realize a just and prosperous society based on Pancasila. Collaboration between families, schools and communities is needed in internalizing the values of Pancasila.